Analisis Pembuatan Jaringan Fiber to the Home (FTTH) di Perum Bumi Karawang Baru - Adam Fatta’ah Ramadhan; Arnisa Stefanie (Peneliti.net, 2023)
Advances in information and communication technology (ICT) have fueled the demand for fast and reliable connectivity. Fiber to the Home (FTTH) is recognized as an effective solution to provide high internet speed and reliable access to users' homes. This study aims to design an optimal FTTH network at Perum Bumi Karawang Baru. The research method involves a literature study to understand the concept of FTTH, network topology analysis, geographic mapping, and analysis of user needs. Network topology analysis identifies key distribution points and plans main routes, while geographic mapping estimates the number of users and distribution of houses in Perum Bumi Karawang Baru. The data is used for fiber optic cable planning and Optical Line Terminal (OLT) placement. Analysis of user needs is carried out to determine the desired internet speed, number of potential users, and other network requirements. FTTH network design includes the selection of OLT devices, Optical Network Units (ONU), and appropriate network components based on this analysis. The result is an FTTH network design with a network topology map, OLT placement, fiber optic cable mapping, and ONU configuration. The goal is to optimize the quality of internet connectivity, meet user needs, and enable easy growth in the future. This research provides practical guidance for related parties in planning and building an FTTH network at Perum Bumi Karawang Baru, so that people can enjoy high internet speed and reliable connectivity to support their digital needs.